(untitled) (CIPEEX, 2022)
INTRODUCTION: IN APRIL 2016, THERE WAS A CHANGE IN THE NOMENCLATURE OF THE TERM PRESSURE ULCER (UP) FOR PRESSURE INJURY (LPP), DUE TO THE GREATER COVERAGE AND THE USE OF ARABIC NUMERALS TO DESCRIBE EACH STAGE RATHER THAN ROMAN NUMERALS . (MORAES ET AL., 2016). THE CONCEPT OF LPP IS A LOCALIZED DAMAGE TO THE SKIN AND / OR UNDERLYING SOFT TISSUE USUALLY ON BONE PROMINENCE OR RELATED TO MEDICAL EQUIPMENT AND DEVICE (MORAES ET AL., 2016). OBJECTIVE: THE OBJECTIVE OF THIS STUDY WAS TO IDENTIFY, IN FRONT OF THE SCIENTIFIC LITERATURE, HOW THE APPROACHES ON PRESSURE INJURIES IN BRAZIL ARE DESCRIBED. METHODOLOGY: BASED ON AN INTEGRATIVE REVIEW OF THE LITERATURE (MENDES; SILVEIRA; GALVAO, 2008), IN THE SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) ELECTRONIC LIBRARY IN THE VIRTUAL HEALTH LIBRARY (VHL), LATIN AMERICAN LITERATURE AND OF THE CARIBBEAN IN HEALTH SCIENCES (LILACS) AND NURSING DATABASES (BDENF), WITH THE HEALTH DESCRIPTORS ULCERA BY PRESSURE. PRESSURE INJURY. NURSING. RESULTS: DATA ANALYSIS RESULTED IN THREE CATEGORIES: CATEGORY 1 CAUSES AND INCIDENCE, IN THE CAUSES AUTHORS POINT TO SOME PROBLEMS SUCH AS: HUMIDITY, IMPAIRED PHYSICAL IMMOBILITY, BASIC DISEASES AND DEHYDRATION; CATEGORY 2 PREVENTIVE MEASURES WERE LISTED BY THE AUTHORS: CHANGE OF POSITION, ADEQUATE NUTRITION, EVALUATION OF THE DEGREE OF RISK, USE OF PROTOCOLS, PROTECTION OF BONY PROMINENCES AND ORIENTATION TO THE FAMILY AND THE PATIENT; CATEGORY 3 NURSING CARE, RESEARCH POINTS OUT KEY POINTS SUCH AS PLANNING CARE ACTIONS, NUTRITIONAL SUPPORT, ANALYSIS AND EXECUTION OF PROTOCOLS FOR INJURIES AND IMPLEMENTATION AND DIAGNOSES. CONCLUSION: PRESSURE INJURIES ARE CONSTANTLY PRESENT IN OUR DAILY LIVES AS NURSING PROFESSIONALS, AND NEED TO BE STUDIED AND IMPLEMENTED BECAUSE THERE ARE STILL HIGH INCIDENCE RATES GENERATING A LOT OF EXPENSE. THE NURSING CARE TO BE IMPLEMENTED IS SELECTED THROUGH THE APPLICABILITY OF THE PATIENT’S RISK ASSESSMENT (SCALES SUCH AS BRADEN), PROTOCOLS, CONTINUING EDUCATION, THE STAGE IN WHICH THE PATIENT IS AND THE NEED FOR EACH. THEREFORE, IN THE MULTIDISCIPLINARY TEAM, NURSES PLAY A FUNDAMENTAL ROLE IN THE ELABORATION OF CARE ACTIONS BASED ON THE SCIENTIFICITY AND PRACTICE OF NURSING CARE.